Sistem Akuntansi Kas Kecil Menggunakan Aplikasi Berbasis Web Pada Koperasi Politeknik Jambi - Arisman Arisman (Journal of Applied Accounting and Business, 2020)
Jambi Polytechnic Cooperative is one of the business units engaged in photocopying documents, printing documents, and buying and selling stationery (ATK). The Jambi Polytechnic Cooperative was established with the aim of improving the academic atmosphere and making it easier for students to complete their needs in the learning and teaching process. The management of expenditure and income data on the Cooperative Petty Cash at the Jambi Polytechnic is still done manually so that the performance in the process of managing expenditure and income data is still not optimal. In order to manage data more optimally, a web-based accounting information system must be used. This research was conducted on petty cash in the Jambi Polytechnic cooperative, the petty cash accounting information system in the Jambi Polytechnic cooperative uses the imprest method or the fixed funds method, where this method is a method which is a method of filling the petty cash always in fixed amount in accordance with the amount at the time of initial formation petty cash fund. The method used by the author is data collection, analysis and designing the system based on the results of research conducted. This research resulted in an application that is equipped with a petty cash position statement and a general journal report where this report is the output of the designed application. The development of the petty cash accounting information system uses the waterfall method and the data flow model used is DFD (Data Flow Diagram), a programming language using PHP, and a MySQL database. This research resulted in a petty cash accounting information system that can be implemented in the Jambi Polytechnic Cooperative.